PENGARUH KOMUNIKASI INTERNAL DAN BEBAN KERJA TERHADAP KEGAIRAHAN KERJA PEGAWAI DINAS KEHUTANAN KABUPATEN KONAWE - Misnawati Misnawati (Jurnal Akrab Juara, 2018)
This study aims to determine and analyze the influence of Internal Communication and Workloads on the Occupational Passion of Konawe District Forestry Service Employees both simultaneously and partially. This research is a type of explanatory research that aims to explain the position of the variables to be studied and the relationship and influence between one variable and another. The results showed that: (1) Internal Communication and Workload simultaneously had a positive and significant effect on the Work Passion of the Konawe District Forestry Service Employees, (2) Internal Communication partially had a positive and insignificant effect on the Excitement of the Workers of the Konawe District Forestry Service, and (3) Workload partially has a positive and significant effect on the Excitement of the Work of the Konawe District Forestry Service Staff. Keywords: Internal Communication, Workload, and Work Excitement